Effect of Binders on Physical and Mechanical Properties of Stainless Steel 316L Alloy Fabricated by Metal Injection Moulding Process - Mohd Faizul Farhan, Ahmad Hamidi; Wan Sharuzi, Wan Harun; Faiz, Ahmad; Abu Bakar, Sulong (Universiti Malaysia Pahang, 2016)
Metal injection moulding (MIM) is a well-known process that provides advantages when making small parts with high density. MIM process can cut down the production costs due to its net-shape fabrication advantages, acceptable for manufacturing small parts, and combining great part complexity with high production quantities. This study compares the effects of two binders and sintering parameters on the mechanical properties of 316L stainless steel (SS) MIM compact. The 316L SS compacts have been fabricated by metal injection moulding (MIM) process using two different binders, known as Binder A, and B. Sintering was carried out under high purity argon atmosphere between 1100°C and 1300°C for 1 and 3 hours. The physical properties were determined from surface roughness testing, and mechanical properties were evaluated by tensile testing. Compacts with binder B recorded greater surface roughness compared to the compacts utilised binder A. Good agreement between the sintering curve and mechanical properties has been found. Compacts that sintered at 1300 °C for 3-hour exhibit highest tensile strength compared to others compacts. By increasing the sintering temperature and sintering time, 316L SS sintered compact recorded better mechanical properties.